Clinical outcome of an anticancer agent screening test with primary culture cells - Hirono, M; Yoshihara, T; Hayashi, Y; Oosaki, T; Hirai, M (Gan to kagaku ryoho, 1999)
Cancer cells are tested for sensitivity to anticancer agents before the drugs are used for treatment in clinical settings, but the results of these tests have not always been reported fully. Since 1973, one of the authors (Hirono) has been performing sensitivity tests of anticancer drugs by using primary culture cells derived from human cancer tissue, taking into account in vivo status and taking great care to reduce the number of procedural errors. From 1991, flow cytometry has also been adopted for use in anticancer drug sensitivity tests. In the present study, the outcomes of cancer patients were compared by dividing them into a group treated only with anticancer agents to which cancer cells had responded in sensitivity tests, and a group treated with other drugs. The subjects consisted of 132 patients with endometrial cancer stage III (n = 26) and IV (n = 10), ovarian cancer stage III (n = 26) and IV (n = 7), peritonitis carcinomatosa (n = 18), and suspected advanced ovarian cancer (n = 45). There was a significant prolongation in median survival time and survival time among the non-survivors according to the results of a Kaplan-Meier analysis. These findings suggest that sensitivity testing of cancer cells to anticancer drugs should be performed before the start of cancer chemotherapy in the clinical setting.